Framework to improve biohydrogen generation with estrogen co-metabolism under complete suppression of nitrogen source. (September 2022) - Syed, Zainab; Sogani, Monika; Sharma, Gopesh; Sonu, Kumar; Rajvanshi, Jayana; Gupta, Nishan Sen
Graphical abstract: Highlights: Co-metabolism of ethynylestradiol (EE2) with glycerol enhances hydrogen production. Enhanced hydrogen production under nitrogen limiting conditions. Different substrate inputs affect the hydrogen production due to metabolic route changes. Enhanced hydrogen production in non-growing conditions than growing conditions. 78% EE2 degradation by Rhodopseudomonas palustris strain MDOC01 in 168 h. Abstract: The current work provides insights for improving the hydrogen output while degrading emerging contaminants using Rhodopseudomonas palustris . The changes in the growth rate of a microorganism due to different substrate inputs affects the hydrogen production due to metabolic route changes. The different ratios of glutamate and glycerol as nitrogen and carbon sources along with the presence of ethinylestradiol (EE2) in the photofermenter affected the flux of electrons being directed towards biosynthesis and biohydrogen generation. The combination of glutamate and glycerol in different ratios (Glu:Gly; 0, 0.20 and 0.54) along with estrogen showed no significant difference in the bacteriochlorophyll concentrations. The highest biomass concentration (0.013 h −1 ) was in ratio of 0.54 while maximum specific hydrogen production (1.9 ± 0.05 ml g −1 biomass h −1 ) was observed under complete suppression of nitrogen (0; without Glu; non-growing condition) with resultant improved estrogen degradation of about 78% in 168 h by R. palustris strain MDOC01.